Desarrollo e implementación de un sitio turístico en plataforma web para PC utilizando sistemas de información geográfica para el cantón Arenillas - Castillo Castillo, Jayaira Lisbeth (2014)
With this research is to solve a problem raised in the canton Arenillas, due to lack of information or outdated data about the natural wealth that has this canton.